The activities of Russian public organizations in China in 1917 (on the example of the Russian colony in Manchuria and Xinjiang) - Elena N. Nazemtseva (RUDN Journal of Russian History, 2019)
The article analyzes activities of Russian public organizations in China in 1917 after the Russian February Revolution of 1917. Previously unstudied archival sources demonstrate that during that period, a large Russian diaspora formed in the Republic of China. Its composition depended on the speciﬁcs of the region. Information about the events in Russia and the revolutionary agitators arriving in China sharply intensiﬁed political life in the Russian colonies. This tendency was most pronounced in Manchuria, where the Chinese Eastern Railway (CER) had a key inﬂuence on the life of the Russian diaspora. Beginning in March 1917, various public organizations and associations began to form here - executive committees, councils of workers’ and soldiers’ deputies, party cells of the RSDLP(b). Throughout the year, rallies, demonstrations, and meetings were held in Harbin in support of the revolution and against the Russian administration of the road; here the sentiment was caution and distrust towards the events in Russia. The destabilization of the political situation caused dissatisfaction of the Chinese authorities and the international community, as it violated the work of the CER and led to the introduction of Chinese troops in Harbin. While in Xinjiang public organizations were less active in 1917 they nevertheless aroused the Chinese leadership’s concern, as agitation could easily lead to serious ethnic conﬂicts, especially multinational East Turkestan had not yet recovered from the 1916 uprising. There were no such organizations in Shanghai, Beijing and Tianjin. However, one of the main consequences of these events was the weakening of Russian positions in China, as well as in the Far East and Central Asia as a whole.